Improvement Strategy for KOTAKU program in Slum Settlements Area in Sidoarjo - Ririn Putri Kusuma; Dian Rahmawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
KOTAKU (City Without Slums) program has been implemented in numerous areas identified as slums settlements, including in Sidoarjo, a city adjacent to Surabaya that has given many services in housing provision including for people who commute from Surabaya city. One of the efforts that must be done to handle the slums is to prevent and improve the quality of life and environment in a slum area to develop sustainable settlements to reach the objectives of Sustainable development (SDGs). One of the cases in this program happened in Tambak Cemandi, Sidoarjo where the slums area consists of 9.75 hectares widespread. The settlement area is located in the coastal area where it experienced a decrease in environmental quality due to a lack of public awareness in maintaining the cleanliness of the environment, most people dispose of garbage and defecation in rivers or ponds, and river conditions are filled with garbage, and not yet provided adequate infrastructure facilities. The article aims to formulate a strategy for improving the quality of slums in Tambak Cemandi, Sidoarjo. The first stage in this research is identifying factors that influence the quality improvement of slum settlements in the case study area using the content analysis method, continued by formulating strategies related to the influenced factors through a qualitative descriptive analysis method. The results showed in this article are strategies considering the influenced factors that are community behaviors, community participation, waste management facilities, sanitation infrastructure provision, road conditions, and population income.